2020
DOI: 10.1186/s12893-020-00811-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect comparison of three different types of transanal drainage tubes after anterior resection for rectal cancer

Abstract: Background: Anastomotic leakage (AL) is one of the most severe early complications after rectal cancer surgery. Many studies and meta-analysis results show that the indentation of transanal drainage tubes (TDT) can prevent and reduce the incidence of AL. However, the size and material of drainage tubes are rarely reported. Herein, we compare the effect of three kinds of TDT and analyze the use of TDT material and size to prevent AL, which may better prevent the occurrence of AL. Methods: The clinical data of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…TDTs are now widely used to prevent anastomotic leakage after rectal surgery [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ]. It was reported that the TDT presented non-inferiority in preventing anastomotic leakage, less operation time and blood loss, no difference in early postoperative complications and less incidence in late complication compared to the ileostomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TDTs are now widely used to prevent anastomotic leakage after rectal surgery [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ]. It was reported that the TDT presented non-inferiority in preventing anastomotic leakage, less operation time and blood loss, no difference in early postoperative complications and less incidence in late complication compared to the ileostomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The kind of tube, size, material, site and length of placement and duration are still controversial. In most studies, a silicon rubber tube was used [ [1] , [2] , [3] , [4] , 7 ], and the tube size ranged from 24 to 32 Fr (about 8−10 mm) [ 1 , 3 , 4 , 7 ]. Luo et al compared different types of TDT, such as a 32-Fr silicone tube, 24-Fr silicone tube and 24-Fr latex tube [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations